Endodontic Management of the Three-Rooted Mandibular First Permanent Molar: a Case Report - Iztok Štamfelj (University of Zagreb. School of Dental Medicine, 2014)
The distal root of the mandibular first permanent molar (MFPM) contains one or two canals. More rarely, the second/third distal canal is found in a separate root in a distolingual (DL) position - a radix entomolaris (RE). In Caucasians, this occurs in less than 4% of cases, but it is equally important to be aware of this possibility. Careful examination of the preoperative periapical radiographs (orthoradial and mesially angled) and inspection of the pulp chamber floor during endodontic management may indicate that this radicular variant is present. RE's lingual inclination and buccolingual curvature must be taken into account during cleaning and shaping of the canal within this root to avoid procedural errors, such as straightening and ledging of the root canal, perforation or instrument fracture. The aim of the present paper was to discuss a case report of a young patient, referred to an endodontic office after a ledge was created by inappropriate instrumentation of a buccolingually curved RE canal.